The Art of Resilience: Post-Traumatic Growth in Selected Poems by Maya Angelou - Hemad, Atyaf Abdulrazzaq (NIU Journal of Social Sciences, 2026)
In this study, the two most famous poems of Maya Angelou, “Caged Bird” and “Still I Rise” are analysed using Post-Traumatic Growth (PTG) as developed by Tedeschi and Calhoun. The poem is usually interpreted in terms of resilience, but this present study posits that resilience is not the only aspect of Angelou's poem. Using the five domains of PTG (relating to others, new possibilities, personal strength, appreciation of life, and spiritual/Existential change), a close-reading methodology, the analysis illuminates the way Angelou's formal features (meter, stanzaic transformation, diction, and rhetorical address) reflect the shift from trauma to growth, rather than simply narrating it. In “Caged Bird” and the cumulative refrain in “Still I Rise,” the transformation from septet to quatrain, and the repetition of the refrain, respectively, provide literary correlates for PTG, placing Angelou's work in a literary genre that embodies growth. The study's implications are for trauma studies, cognitive literary studies and African American criticism, and provide a model which could be replicated in the reading of poetry using the PTG framework.